2010
DOI: 10.1002/cncr.25041
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of weight loss during radiotherapy in patients with stage I or II head and neck cancer

Abstract: BACKGROUND:The purpose of the study was to identify predictors of weight loss during radiotherapy (RT) in patients with stage I or II head and neck (HN) cancer. METHODS: This study was conducted as part of a phase 3 chemoprevention trial. A total of 540 patients were randomized. The patients were weighed before and after RT. Their baseline characteristics, including lifestyle habits, diet, and quality of life, were assessed as potential predictors. Predictors were identified using multiple linear regressions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 50 publications
4
43
0
1
Order By: Relevance
“…In part, this has been exacerbated by a change in resting energy expenditure, which furthers the loss of lean body mass seen during and immediately after treatment [11,15]. Predictors of excessive weight loss during treatment include higher weight at baseline, dysphagia at diagnosis, and higher stage tumors [16]. More specifically, a recent study from Denmark reported that patients with a body mass index (BMI) ≥ 25 are three times more likely to lose more than 5 % of baseline weight than patients with BMI < 25 (p < 0.0001) [12].…”
Section: Main Textmentioning
confidence: 99%
“…In part, this has been exacerbated by a change in resting energy expenditure, which furthers the loss of lean body mass seen during and immediately after treatment [11,15]. Predictors of excessive weight loss during treatment include higher weight at baseline, dysphagia at diagnosis, and higher stage tumors [16]. More specifically, a recent study from Denmark reported that patients with a body mass index (BMI) ≥ 25 are three times more likely to lose more than 5 % of baseline weight than patients with BMI < 25 (p < 0.0001) [12].…”
Section: Main Textmentioning
confidence: 99%
“…According to previous reports, numerous quality-of-life dimensions significantly correspond to body weight loss, 22 and scores of global quality of life are lower in patients with more than 10% weight loss. 23 In addition, there is deterioration of physical function and role function 3 months after surgery for oral cancers, which correlates with reduced body image because of a significant decrease in oral function.…”
Section: Discussionmentioning
confidence: 82%
“…Approximately 60% of patient's present weight loss and chronic malnutrition affects approximately 20-57% of patients with head and neck neoplasia, reason why and early enteral feeding must be started to avoid or at least reduce complications and comorbidities [1,11,12,18,19,[26][27][28][29]. Nutritional assessment and intervention should be an integral part of treatment since this complication can lead to compromised treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…This group disserves particular attention since tumoral seeding in gastrostomy stomas have been reported [13][14][15][16][17], primary from the oropharynx, hypopharynx, oral cavity and larynx. Being the pull technique the most associated with metastases reports, reason why new methods for gastrostomy placement have been studied, especially for the ones that require pre-surgical feeding or for nutritional feeding after mayor head and neck surgical intervention [12,18,19]. With this purpose, general surgery and gastroenterology departments of the Fundación Santa Fé University Hospital of Bogotá Colombia presents an alternative technique: Direct puncture endoscopic assisted Gastrostomy reducing the risk of tumoral cell implant at the path and stoma.…”
Section: Introductionmentioning
confidence: 99%